Socio-legal and historical background of the criminalization of illegal interference with personal data - Vabischevich, Vitaly V (Journal of the Belarusian State University. Law, 2020)
The article analyzes the social and legal prerequisites for the introduction of criminal liability for interference in personal data, as well as the historical aspect of formation of the institute of personal data and its protection. The main prerequisites include unsystematic and incomplete legal regulation of the sphere of turnover of personal data, the lack of specific measures of responsibility for attacks on them, advanced the development of information and communication technologies in comparison with the response of legislative and law enforcement agencies to the commission of offenses in this area, the scale of illegal use of personal data and others. The introduction of criminal liability for interference with personal data is an important element in the prevention of crimes in this area, because it contributes to the effective implementation of legislation on personal data. Specific measures of liability, including the limits of their criminalization, should be established depending on the damage caused, including moral damage, to a particular citizen, business entity, society and national security.
Keywords: personal data; protection of information; improvement of legislation; constitutional rights; information security; information technologies; attacks on personal data